A MODERATING VARIABLE FOR THE DEVELOPMENT OF LECTURER PERFORMANCE ANTECEDENTS AND THEIR IMPACT ON GRADUATES' COMPETENCE THROUGH THE LEARNING ENVIRONMENT - Sri Ridma Ramadhani; Mahesa Vicky Satria Ramadhan Lihu; Candra Kusuma Negara (Jurnal Ekonomi, 2022)
Due to the adoption of the ASEAN Economic Community, competition for university graduates in Indonesia is increasingly more intense (AEC). Additionally, job seekers from ASEAN nations are now filling the demand for university graduates who are competent in their fields, in addition to Indonesian youth. Private universities are more prevalent than State Universities as institutions of higher learning. This study aims to identify and analyze the predisposing elements that influence graduate competence, such as foundation management, university administration, dean leadership, lecturer performance, and learning environment. A systematic questionnaire is used to collect data for this investigation. Students' perceptions of the variables under study are captured in the data. One hundred forty-seven students from the Faculty of Economics Management Science Study Program served as the study's samples, representing 9 (nine) private universities. Structural Equation Modeling and descriptive statistics are utilized to analyze the processed data (SEM). The study's findings are: (1) Foundation management positively and significantly influences university governance; (2) Foundation management positively and significantly influences the Dean's leadership; (3) Foundation management positively and significantly influences lecturer performance; (4) University governance positively and significantly influences lecturer performance, and (5) University governance positively and significantly influences lecturer performance.